Pengembangan Strategi Metropolitan Cirebon Raya (MCR) dalam Mengantisipasi Dampak Lingkungan - Erna Erna; Sumaryono Sumaryono (Journal of Communication Sciences (JCoS), 2020)
In this study, a community marketing approach was carried out in the development of the Greater Cirebon Metropolitan (MCR) to anticipate environmental impacts. Metropolitan is defined as a stand-alone area or a core urban area with surrounding urban areas having functional linkages connected to an integrated regional infrastructure network system with a total population of at least one million people. The development of MCR has the concept of developing Cirebon's historical culture with the leading sectors of tourism, trade, industry and crafts. Cirebon's leading tourism sector is based on cultural, religious and culinary tourism. Featured in the industrial and handicraft sector at MCR include: Seafood processing industry, agro industry, rattan furniture, food and beverage home industry, batik, earthenware carving, shell craft, natural stone. The development of the MCR is accelerated by the ease of accessibility of transportation modes. The development of MCR leads to filling the space that has been built by the transportation network to its satellite cities. Among the activities to fill the space are the potential for superior economic business in the form of hotel services, culinary businesses, trade, industry and crafts. Community marketing can be used as an instrument to control the negative environmental impacts of the presence of buildings or economic activities that can harm the community, such as floods in the rainy season and lack of clean water during the dry season, increased waste and traffic over crowded. Alternative instruments outside the regulation are in the form of building collective awareness of various parties to prevent the impact of environmental damage from the development of Metropolitan Cirebon Raya (MCR).